2016
DOI: 10.1093/nar/gkw349
|View full text |Cite
|
Sign up to set email alerts
|

G-rich telomeric and ribosomal DNA sequences from the fission yeast genome form stable G-quadruplex DNA structuresin vitroand are unwound by the Pfh1 DNA helicase

Abstract: Certain guanine-rich sequences have an inherent propensity to form G-quadruplex (G4) structures. G4 structures are e.g. involved in telomere protection and gene regulation. However, they also constitute obstacles during replication if they remain unresolved. To overcome these threats to genome integrity, organisms harbor specialized G4 unwinding helicases. In Schizosaccharomyces pombe, one such candidate helicase is Pfh1, an evolutionarily conserved Pif1 homolog. Here, we addressed whether putative G4 sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 63 publications
(103 reference statements)
4
75
0
Order By: Relevance
“…In the absence of Pfh1, replication forks pause at G-quadruplexes, leading to DNA damage and genome instability [28]. A recent paper shows that, both telomeric and rDNA sequences from S. pombe , can form G-quadruplexes in vitro and that Pfh1 is able to unwind these structures [179]. Interestingly, a study suggested that G-quadruplexes not only pose replicative obstacles but also function as regulatory elements that aid in lagging-strand synthesis [180], and emerging evidence suggest the role as cis -acting regulatory elements of G-quadruplexes in DNA replication as well as in transcription, translation, and telomere maintenance [181].…”
Section: Replication Barriers Associated With Repeat Dna and Protementioning
confidence: 99%
“…In the absence of Pfh1, replication forks pause at G-quadruplexes, leading to DNA damage and genome instability [28]. A recent paper shows that, both telomeric and rDNA sequences from S. pombe , can form G-quadruplexes in vitro and that Pfh1 is able to unwind these structures [179]. Interestingly, a study suggested that G-quadruplexes not only pose replicative obstacles but also function as regulatory elements that aid in lagging-strand synthesis [180], and emerging evidence suggest the role as cis -acting regulatory elements of G-quadruplexes in DNA replication as well as in transcription, translation, and telomere maintenance [181].…”
Section: Replication Barriers Associated With Repeat Dna and Protementioning
confidence: 99%
“…In vitro, nuclear Pfh1 binds to a telomeric DNA substrate consisting of GGGTTACA telomeric repeats (Wallgren et al 2016). Because pfh1 + is an essential gene (Tanaka et al 2002; Zhou et al 2002), spore clones from pfh1Δ strains divide only 1–3 times, and these strains show stable but shorter telomeres than wild-type cells (Zhou et al 2002).…”
Section: Pfh1 Promotes Replication At Hard-to-replicate Sitesmentioning
confidence: 99%
“…These sequences were selected from the S. pombe genome and are predicted to form G4 structures in vivo. [10] The sequence of the cdc13 + -promoter DNA is an evolutionarily conserved G4 motif and is found in all four avail-able fission yeast genomes. [10] However,t he sequences of the previously studied oligonucleotides started with at en-nucleotide poly-A tail, in contrast to the oligonucleotides studied herein.…”
Section: Selection Of Oligonucleotides For Htsmentioning
confidence: 99%
“…[7] The positions of G4 motifs are not randomly placed in the genome,b ut are enriched at specific regions.F or instance, the G4 motif-enrichedf eatures in S. pombe include ribosomal DNA (rDNA), promoters, telomeres, 5' and 3' untranslatedr egions( UTRs), nucleosome-depleted regions, [8] and some origins of replication . [10] Theses tudies, conducted in vitro, demonstrated that the rDNA G4 motif adopts an intermolecular G4 structure and that the telomeric G4 motif adopts an intramolecular G4 structure. [10] Theses tudies, conducted in vitro, demonstrated that the rDNA G4 motif adopts an intermolecular G4 structure and that the telomeric G4 motif adopts an intramolecular G4 structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation